Work Motivation of Educational Personnel in Improving the Effectiveness of Academic Administration Services - Meti Wigiyantini; Undang Ruslan Wahyudin; Ine Rahayu Purnamaningsih (Universitas Negeri Semarang, 2025)
This study aims to examine the motivation of educational staff in improving the effectiveness of academic administration services in higher education institutions during the digital transformation. Educational staff play a strategic role in ensuring the accuracy, timeliness, and quality of academic administration processes, which in turn affect the efficiency of institutional management and the overall student experience. This study utilised a qualitative method by conducting a systematic review of 23 sources, including scientific articles, academic books, and policy documents published between 2020 and 2025. The literature selection process was carried out in several stages: (1) conducting an initial search using keywords related to work motivation and academic administration, (2) filtering sources based on predetermined inclusion criteria, publications written in Indonesian or English, relevant to the context of educators, and published within the specified time period, and (3) eliminating duplicate entries, non-scientific material, and references that lacked sufficient empirical or conceptual content. All sources that met the eligibility criteria were analysed using thematic analysis techniques, which included initial coding, theme grouping, and synthesis of findings to identify patterns, core concepts, and relationships between variables related to the work motivation of educators in higher education. Thematic analysis reveals that work motivation is shaped by intrinsic factors such as the importance of work, obligations related to public service, and opportunities for professional advancement and extrinsic factors, including reward systems, organisational work environment, and proportional workload. The results of the study show that the effectiveness of academic administration services is influenced by three main groups of factors: (1) intrinsic motivation, such as a sense of meaning in work and a moral commitment to serve; (2) extrinsic motivation, including reward systems, workload, and work environment support; and (3) Public Service Motivation (PSM), which plays a role in strengthening the dedication of educational personnel to service management. The literature synthesis also reveals that motivation only has an optimal impact when supported by strong human resource management, participatory leadership, and adequate digital competence. Thus, the findings of this study directly confirm the relationship between work motivation and the effectiveness of academic services, while also providing strategic direction for universities in designing interventions to improve service quality.